2013
DOI: 10.1093/icesjms/fst068
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for alternative migratory behaviours in the northern Gulf of St Lawrence population of Atlantic cod (Gadus morhua L.)

Abstract: Le Bris, A., Fréchet, A., Galbraith, P. S., and Wroblewski, J. S. 2013. Evidence for alternative migratory behaviours in the northern Gulf of St Lawrence population of Atlantic cod (Gadus morhua L.). – ICES Journal of Marine Science, 70: 793–804. Inter-individual variation in migration propensity affects population dynamics and connectivity. The diversity of migratory behaviours of Atlantic cod (fork length >40 cm) in the northern Gulf of St Lawrence was studied using data-storage tags that record depth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…For example, in addition to spawning rises in Pacific halibut [4,7], data derived from physically recovered PSATs are generally examined separately from analyses of received data series, with archived data used to quantify vertical movement rates of billfishes [24,39]. The archived data were better at revealing patterns of irregular post-release behaviour in large pelagic fishes than the satellite-derived data [35], and only archived data could identify highfrequency oscillating dives in Atlantic Bluefin tuna [28]. Archived data from PSAT-tagged Pacific halibut have recently been used to classify periodic behaviour and quantify the influences of biological and physical drivers [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in addition to spawning rises in Pacific halibut [4,7], data derived from physically recovered PSATs are generally examined separately from analyses of received data series, with archived data used to quantify vertical movement rates of billfishes [24,39]. The archived data were better at revealing patterns of irregular post-release behaviour in large pelagic fishes than the satellite-derived data [35], and only archived data could identify highfrequency oscillating dives in Atlantic Bluefin tuna [28]. Archived data from PSAT-tagged Pacific halibut have recently been used to classify periodic behaviour and quantify the influences of biological and physical drivers [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous characterizations of Canadian Atlantic halibut spawning behaviours and time periods have been derived from samples outside of the Gulf [41]; therefore, the identification of Gulf halibut spawning locations remains a research question of interest to Atlantic halibut assessment and management [31]. Our PSAT archived data are currently being investigated against seasonal bathymetric and temperature data to model the movements of Atlantic halibut within the Gulf of St. Lawrence over an annual cycle [36], using techniques first applied to Atlantic cod [35]. A necessary feature for modelling halibut movements over an annual cycle is continuous depth and temperature records, such that daily estimates of location can be estimated from prior location and seasonal hydrographic variables [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapidly improving technology is opening new possibilities for observing behaviors that were unthinkable just a few decades ago. Methods include active fisheries acoustics (sonars and echo sounders, e.g., Handegard & Tjøstheim 2005), acoustic tracking (e.g., Langård et al 2015), and data storage tags (e.g., Le Bris et al 2013). However, behavioral observations using these methods tend to be one-off studies; only fisheries acoustics are widely used in routine monitoring, and then not for monitoring behavior, but spatial distribution and abundance.…”
Section: Life-history Traitsmentioning
confidence: 99%
“…Age-based movements could be related to age-specific maturation and learned behaviors regarding schooling, optimal foraging, and spawning locations. For some species, such as Atlantic cod, Gadus morhua , there are multiple groups within a population which display different migratory patterns hypothesized to have been learned from older fish [1012]. MacCall [13] concluded that the loss of “migratory knowledge” within a population could cause a change in fitness leading to stock decline.…”
Section: Introductionmentioning
confidence: 99%